PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN YANG TERDAFTAR DI BEI TAHUN 2013 - Arfian Fauzi; Nurmatias Nurmatias (Ekonomi dan Bisnis, 2015)
This study was conducted to examine the effect of Profitability (ROE), Leverage (DER) and Dividend Policy (DPR) on Firm Value (PBV) of listed companies in the ISE period 2013. The population in this study is from whole companies which listed in ISE during 2013 period. Data is taken from the company’s financial reports. Gained of total sample 50 companies. The analysis technique is using path analysis with multiple linear regression and single regression. Hypotesis test is using F test, t test, and R2 test with level of significance 5%. The results showing that Profitability (ROE) has no significance influence on Dividen Policy (DPR), Leverage (DER) has significance influence on Dividend Policy (DPR). Profitability (ROE) has significance influence on Firm Value (PBV), Leverage (DER) and Dividend Policy has no significance influence on Firm Value (PBV). We suggest to investors in Indonesia Stock Exchange to notice another factors that influence the Firm Value (PBV) in making decision of investments. The Profitability variable (ROE) in this study has the most influence on Firm Value variable (PBV), which proven by smaller number of t-count than t-table and has significance number 0,000.